KONDISI FISIK TANAH DI BAWAH TEGAKAN PINUS (Pinus merkusii Jungh. et de Vriese) DAN PADANG RUMPUT DESA WATUTAU KECAMATAN LORE PEORE KABUPATEN POSO SULAWESI TENGAH - kasih, Gabriella Cahya; Yusran, Yusran; Zulkaidhah, Zulkaidhah (Universitas Tadulako, 2019)
Watutau Village is one of the villages in the Napu valley plains of Central Sulawesi, can be found stands pine breadth Â± 500ha. In addition to pine stands there are also grasslands, which are located adjacent to pine stands, it attracts attention for research because it has two distinct land cover vegetations. Differences in vegetation composition of land cover can also affect the physical condition of the soil. The purpose of this study was to determine the physical condition of the soil under the stands of pine and grassland. The study was conducted from November 2017 till January 2018, located in Watutau Village, Lore Peore Sub-district, Poso District, Central Sulawesi. This research starts from field survey, location determination, soil sampling, analysis of soil sampled laboratory. Determination of location done purposive sampling by considering slope condition that is section of valley, slope and peak. Soil sampling is done at two depths 0-30cm and 30-60cm. The results showed that the soil under pine stands had dust clay soil texture and clay, granular soil structure, bulk density 1.26gr / cm3 (High) and 1.3gr / cm3 (High), porosity 50.2% (Good) and 48.6% (Less good). Permeability 2.45cm / hr (Medium) and 2.9cm / hr (Medium), soil colors yellowish red, very dark gray, gray irish, very dark grayish brown, grayish brown. While the soil conditions in the grassland area have clay soil texture, granular soil structure, Bulk density 1,34gr / cm3 (High) and 1,4gr / cm3 (Very High), 50% Porosity (Good) and 47,63% Not good), Permeability 2.14cm / hr (Medium) and 3.66cm / hr (Medium), soil colors dark grayish brown color, brown, strong brown.